2012
DOI: 10.1080/07347332.2012.664258
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Evaluation of the Impact of Structured Child-Centered Interventions on Psychiatric Symptom Profile of Parents with Serious Somatic Illness: Struggle for Life Trial

Abstract: This is a trial of cancer patients who are seriously somatically ill and of how their distress affects their spouse or children. In the pilot phase the authors examined whether there are changes in psychiatric symptom profile of seriously somatically ill and healthy parents between assessments concerning a situation before the onset of parental illness, in current situation before intervention and 4 months after the intervention. The study is a family cluster, randomized, controlled treatment trial for parents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
65
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(67 citation statements)
references
References 42 publications
2
65
0
Order By: Relevance
“…In a previous study, children, parents, and health professionals reported that interventions had several positive impacts on children's and parents' psychosocial well-being [31]. Work is underway to transfer well-established family intervention programs from psychiatric to somatic care [32], the need for which is confirmed by this study.…”
Section: Discussionsupporting
confidence: 65%
“…In a previous study, children, parents, and health professionals reported that interventions had several positive impacts on children's and parents' psychosocial well-being [31]. Work is underway to transfer well-established family intervention programs from psychiatric to somatic care [32], the need for which is confirmed by this study.…”
Section: Discussionsupporting
confidence: 65%
“…The quality of studies varied from weak to strong. All of the studies were developed and delivered in Europe: Norway (Bugge et al, ), Denmark and Germany (Thastum et al, ), Finland (Niemelä, Repo, Wahlberg, Hakko, & Räsänen, ), and France (Landry‐Dattée et al, ). There were two qualitative studies with no control group (Bugge et al, ; Landry‐Dattée et al, ): a quantitative randomised controlled trial (Niemelä et al, ) and a semi‐controlled mixed methods design study (Thastum et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…All of the studies were developed and delivered in Europe: Norway (Bugge et al, ), Denmark and Germany (Thastum et al, ), Finland (Niemelä, Repo, Wahlberg, Hakko, & Räsänen, ), and France (Landry‐Dattée et al, ). There were two qualitative studies with no control group (Bugge et al, ; Landry‐Dattée et al, ): a quantitative randomised controlled trial (Niemelä et al, ) and a semi‐controlled mixed methods design study (Thastum et al, ). One of the studies focused exclusively on parents with end‐stage cancer (Bugge et al, ) and the remaining three studies included—but was not limited to—parents with end‐stage cancer (Landry‐Dattée et al, ; Niemelä et al, ; Thastum et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Clinical trials of innovative interventions with children living with parental illness have targeted those living with parental psychiatric illnesses (Beardslee et al, 1997) and parental terminal illness (Niemela, Repo, Wahlberg, Hakko, & Rasanen, 2013). To date, there is no research examining the effects of evidence-based interventions on reducing negative outcomes (e.g., internalizing and externalizing symptoms) and promoting development of strengths and competencies in children living with parental CNCP.…”
mentioning
confidence: 99%